IDDF2018-ABS-0219 Assessment of correlation between non-alcoholic fatty liver disease and severity of coronary artery disease in young acute coronary syndrome patients. (June 2018) - Ali, Alyaa Hassan; Faizal, Shawal Mohamed; Muhammad Nawawi, Khairul Najmi; Zhiqin, Wong; Soon, Ngiu Chai; Yaacob, Nur Yazmin; Shah, Shamsul Azhar; Che Hassan, Hamad Hamdi; Maskon, Oteh; Raja Ali, Raja Affendi
Abstract : Background: Coronary artery disease (CAD), which clinically manifested as an acute coronary syndrome (ACS) is an important extrahepatic cardiovascular complication of non-alcoholic fatty liver disease (NAFLD). To date, little is known about the correlation between young patients with ACS and NAFLD. Aim to assess the correlation between NAFLD and severity of CAD in young ACS patients and determine the prevalence of NAFLD in this cohort. Methods: This cross-sectional study included young (45 years and less) ACS patients. Coronary angiogram was performed to assess CAD severity, and complexity determined by SYNTAX score. CAD severity was classified into: no apparent CAD, mild CAD, single vessel disease (SVD) and multi-vessel disease (MVD). Liver ultrasound was used to diagnose and grade the NAFLD (grade 1–3). NAFLD fibrosis score (NFS) was calculated, and patients were stratified to low, indeterminate, and high probability for advanced liver fibrosis. Results: Total of 85 patients with median age of 40 years (IQR 35–43) and predominated by males (84.7%). Thirty-three (38.9%) had ST elevation myocardial infarction (STEMI), 32 (37.6%) had Non-STEMI and 20 (23.5%) had unstable angina. MVD was demonstrated in 36.5%, SVD in 24.7%, mild CAD in 31.8%, and no apparent CAD in 7.1% of the patients. Median Syntax score was 16 (IQR 9.0–22.3). NAFLD was diagnosed in all, 85 (100%) patients, with 13 (15.2%), 36 (42.4%) and 36 (42.2%) patients had grade 1, 2 and 3 liver steatosis respectively. NFS detected low advanced fibrosis probability in 60 (70.6%) patients, indeterminate probability in 24 (28.2%) patients and high probability in only 1 (1.2%) patient. No significant correlation between grades of NAFLD with ACS subtypes (p=0.72), severity of CAD (p=0.882) and SYNTAX score (p=0.982). No significant association between NFS and ACS subtypes (p=0.232), severity of CAD (p=0.445) and SYNTAX score (p=0.624, r=0.07). Conclusions: NAFLD is highly prevalent in young patients presented with ACS, and it should be routinely screened in our clinical practice. However, in a small cohort, we observed no significant correlation between severity of NAFLD and severity of CAD among young ACS patients.